Is the case-mix of patients who self-present to ED similar to general practice and other acute-care facilities?. Issue 12 (28th August 2013) - Harris, Tim; McDonald, Keith
Abstract : Objective: To benchmark walk-in presentations to emergency departments (ED) with those presenting to other local acute healthcare facilities. Setting: A large teaching hospital with an annual ED census of 140 000 adult patients and surrounding associated acute healthcare providers. Methods: A random sample of 384 patients who self-presented to the ED was obtained. Benchmarking data were drawn from two general practices; the Tower Hamlets Community Services walk-in centre (co-located on-site with the ED) and the GP-run out-of-hours service. Results: The case-mix presenting to the ED was characterised by a higher proportion of injuries and chest pain, but fewer simple infections and non-traumatic musculoskeletal conditions as compared to other acute care facilities in our region. Conclusions: Patients with injuries and possible cardiac chest pain were more likely to attend the ED, and those with infection or musculoskeletal problems less likely, as compared with other acute healthcare facilities. The population presenting to the ED is distinct from that presenting to general practice, out-of-hours clinics, or walk-in centres.